Digital Anxiety among Students of the Special Education Department, College of Basic Education – University of Babylon - العكاشي, مريم عبد الحسين جاسم; الربيعي, شوق صاحب عزيز (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The current research aims to explore digital anxiety among students in the Department of Special Education at the University of Babylon - College of Basic Education. The research sample was determined to be (120) male and female students from the Department of Special Education. The researchers adopted the Digital Anxiety Scale (Abdul Hussein, 2018), which addressed fear and embarrassing concerns that can affect an individual's interaction with digital world programs on the internet. The scale consists of (35) items. The researchers then verified the apparent validity of the scale, its construct validity, and its reliability. The current research aimed to identify: The results for the first objective showed that students in the department experience digital anxiety, with the calculated value being (5.591) compared to the tabular value (1.96). This indicates that special education students suffer from digital anxiety. The results for the second objective showed that females are more anxious than males, as measured by the gender variable, with the calculated value for the two independent samples being (1.536) compared to the tabular value (1.96). The researchers concluded with a set of conclusions and recommendations: 1.Deliver lectures to introduce students to the concept of digital anxiety and its impact on the individual's personality, its development, and its path. publications. The researchers suggest: Conduct studies addressing digital anxiety among government employees and groups.